Pengaruh PDRB dan Tingkat Pengangguran Terhadap Kemiskinan di Sumatera Utara Periode 2005-2019 - Dwitya Nafa Syafrina; M Iqbal Pratama (Journal of Trends Economics and Accounting Research, 2020)
Economic growth is a benchmark in knowing how advanced and developing a region is. The purpose of this study was to determine the effect of GRDP and unemployment rate on poverty in North Sumatra for the period 2005 - 2019. Secondary data obtained were documents, namely from BPS. Data analysis using the classical assumption test includes normality test, heteroscedasticity test, linearity test, multicollinearity test and autocorrelation test and multiple regression test. The results of the calculation of the hypothesis test using the t test, the PDRB variable has no effect on economic growth, while the unemployment variable has a positive and significant effect on poverty.